KOMITMEN ORGANISASI DAN DESENTRALISASI SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN PADA KINERJA MANAJERIAL - Mike Ratnasari, Ni Ketut Ayu; Pradnyantha Wirasedana, I Wayan (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
Performance of the individuals in managerial activities that includes planning, supervision, staff selection, negotiation, and representation that reflects the overall performance of managers. The purpose of this research was to determine whether there is influence between budget participation on managerial performance, organizational commitment and decentralization as a moderating. The population used in this study were all employees at six units of PT. PLN Distribution of Bali for the fiscal year 2016. The sample was 73 determined using nonprobability sampling with purposive sampling technique. The research data come from questionnaires distributed to respondents and data analysis technique used is a simple linear regression analysis and regression analysis moderation. Based on the results of their research analysis found a positive effect of budget participation on managerial performance. Organizational commitment variable and variable decentralization has not been able to strengthen the influence of budget participation on managerial performance.
Keywords: Participation Budgeting, Managerial Performance, Organizational Commitment, Decentralization